2012
DOI: 10.5301/ru.2012.9391
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: The gynecologist's opinion

Abstract: Endometriosis: the gynecologist's opinion Endometriosis is defined as the presence of endometrial glands and stroma outside the uterine cavity. Endometriosis affects 7- INTRODUZIONESi definisce endometriosi la presenza ectopica di tessuto endometriale, nelle sue componenti ghiandolare e stromale, in sedi differenti dalla cavità uterina. Rappresenta una delle più comuni patologie ginecologiche interessando il 7-10% delle donne in età riproduttiva, il 25-50% delle donne sterili ed il 60% delle pazienti con disme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
6
0
3
Order By: Relevance
“…Moreover, Signorile et al's data [206] showed the ectopic presence of primitive endometrium, expressing both CA125 and oestrogen receptor, in 11% of female foetuses (4/36). Focusing on this evidence, we have to consider also that endometriosis affects approximately 10% of women in reproductive age [13, 14], and moreover that retrograde menstruation could be observed in 90% of endometriosis-free women in reproductive age with pervious fallopian tubes. Taking all together, all these pieces of evidence allow us to argue that the ectopic presence of primitive endometrium in female foetuses and the presence of endometriotic implants in women of reproductive ages are quite similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Signorile et al's data [206] showed the ectopic presence of primitive endometrium, expressing both CA125 and oestrogen receptor, in 11% of female foetuses (4/36). Focusing on this evidence, we have to consider also that endometriosis affects approximately 10% of women in reproductive age [13, 14], and moreover that retrograde menstruation could be observed in 90% of endometriosis-free women in reproductive age with pervious fallopian tubes. Taking all together, all these pieces of evidence allow us to argue that the ectopic presence of primitive endometrium in female foetuses and the presence of endometriotic implants in women of reproductive ages are quite similar.…”
Section: Discussionmentioning
confidence: 99%
“…The risk appears to decrease for personal habits that may relate to decreased estrogen levels (i.e., smoking, exercise). Approximately 10% of women in reproductive age are estimated to be affected by this disease [13, 14] and its symptoms, which include acute or chronic pelvic pain (CPP) and abnormal bleeding [12]. Pelvic pain could be expressed as dysmenorrhea, dyspareunia, dysuria, dyschezia, and nonmenstrual chronic pelvic—abdominal muscle pain [15].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of women in reproductive age are estimated to be affected by this disease (4,5). Its symptoms and signs include acute or chronic pelvic pain, abnormal bleeding, infertility (6).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of women in reproductive age are estimated to be affected by this disease [4, 5]. Common symptoms are acute or chronic pelvic pain and abnormal bleeding [6].…”
Section: Introductionmentioning
confidence: 99%